Систематичний огляд роду Larix Mill. у зв’язку з інтродукцією в Україні - Mordatenko, I.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
It is tracked history of studying of genus Larix Mill., the basic systematical classifications of this genus are listed, and the differentiation of kinds of larches in Ukraine on E.G. Bobrov's classification (1972) is lead.